2020
DOI: 10.1016/s2665-9913(20)30177-6
|View full text |Cite
|
Sign up to set email alerts
|

Anakinra for patients with COVID-19

Abstract: e383 damage. Interestingly, in the context of other coronaviruses, NLRP3 activa tion has been shown to trigger cytokine storms. 5 This observation suggests that there is an interplay between SARS-CoV2, autophagy, and cytokine release, and we propose that in future trials, combining anakinra with autophagy inhibitors should be avoided in patients with COVID-19 and evidence of hyperinflammation. It is also reasonable to hypothesise that a combination of anakinra and an autophagy activator should be explored. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Ruxolitinib and anakinra are the other immunomodulatory drugs used in the on-going clinical trials for treating COVID-19 patients [52] , [53] .…”
Section: Resultsmentioning
confidence: 99%
“…Ruxolitinib and anakinra are the other immunomodulatory drugs used in the on-going clinical trials for treating COVID-19 patients [52] , [53] .…”
Section: Resultsmentioning
confidence: 99%
“…Merging various treatment options such as low-dose systematic corticosteroids and anti-viral drugs have been utilized for COVID-19 [64]. Several other treatment methods are also reported, including hydroxychloroquine [65], tocilizumab [66], convalescent plasma (immunotherapy) [67], and favipiravir (RdRp inhibitor) [68], remdesivir [69], anakinra [70], and dexamethasone [71] etc.…”
Section: Lack Of Vaccination and Definitive Treatmentmentioning
confidence: 99%
“…patients [70]. Studies have shown promising results upon treating severely affected patients with these IL-receptor antagonists.…”
Section: Use Of Monoclonal Antibodies and Therapeutic Proteinmentioning
confidence: 99%